A novel liver zonation phenotype-associated molecular classification of hepatocellular carcinoma - Zhang, Tao; Gu, Jian; Wang, Xinyi; Lu, Yaoyao; Cai, Kailin; Li, Huili; Nie, Yingli; Chen, Xiangdong; Wang, Jiliang (Frontiers in Immunology, 2023)
Background: Liver zonation is a unique phenomenon that liver exhibits distinct functions among hepatocytes along the lobule radial axis. Such a phenomenon can cause the sectionalized initiation of several liver diseases, including hepatocellular carcinoma (HCC). However, few studies explored the zonation features of HCC. Methods: Four single-cell RNA sequencing datasets were used to identify hepatocyte-specific zonation markers. Then, integrative analysis was performed with a training RNA-seq cohort (616 HCC samples) and an external validating microarray cohort (285 HCC samples) from International Cancer Genome Consortium, The Cancer Genome Atlas, Gene Expression Omnibus, and EMBL's European Bioinformatics Institute for clustering using non-negative matrix factorization consensus clustering based on zonation genes. Afterward, we evaluated the prognosis value, clinical characteristics, transcriptome and mutation features, immune infiltration, and immunotherapy response of the HCC subclasses. Results: A total of 94 human hepatocyte-specific zonation markers (39 central markers and 55 portal markers) were identified for the first time. Afterward, 3 subgroups of HCC, namely Cluster1, Cluster2, and Cluster3 were identified. Cluster1 exhibited a non-zonational-like signature with the worst prognosis. Cluster2 was intensively associated with a central-like signature and exhibited low immune infiltration and sensitivity toward immune blockade therapy. Cluster3 was intensively correlated with a portal-like signature with the best prognosis. Finally, we identified candidate therapeutic targets and agents for Cluster1 HCC samples. Conclusion: The current study established a novel HCC classification based on liver zonation signature. By classifying HCC into three clusters with non-zonational-like (Cluster1), central-like (Cluster2), and portal-like (Cluster3) features, this study provided new perspectives on the heterogeneity of HCC and shed new light on delivering precision medicine for HCC patients.